Neurosteroid‐mediated regulation of brain innate immunity in HIV/AIDS: DHEA‐S suppresses neurovirulence. Issue 2 (12th November 2012) - Maingat, Ferdinand G.; Polyak, Maria J.; Paul, Amber M.; Vivithanaporn, Pornpun; Noorbakhsh, Farshid; Ahboucha, Samir; Baker, Glen B.; Pearson, Keir; Power, Christopher
Abstract : Neurosteroids are cholesterol‐derived molecules synthesized within the brain, which exert trophic and protective actions. Infection by human and feline immunodeficiency viruses (HIV and FIV, respectively) causes neuroinflammation and neurodegeneration, leading to neurological deficits. Secretion of neuroinflammatory host and viral factors by glia and infiltrating leukocytes mediates the principal neuropathogenic mechanisms during lentivirus infections, although the effect of neurosteroids on these processes is unknown. We investigated the interactions between neurosteroid‐mediated effects and lentivirus infection outcomes. Analyses of HIV‐infected (HIV + ) and uninfected human brains disclosed a reduction in neurosteroid synthesis enzyme expression. Human neurons exposed to supernatants from HIV + macrophages exhibited suppressed enzyme expression without reduced cellular viability. HIV + human macrophages treated with sulfated dehydroepiandrosterone (DHEA‐S) showed suppression of inflammatory gene ( IL‐1 β, IL‐6, TNF‐ α) expression. FIV‐infected (FIV + ) animals treated daily with 15 mg/kg body weight. DHEA‐S treatment reduced inflammatory gene transcripts ( IL‐1 β, TNF‐ α, CD3 ε, GFAP ) in brain compared to vehicle‐(β‐cyclodextrin)‐treated FIV + animals similar to levels found in vehicle‐treated FIV – animals. DHEA‐S treatment also increased CD4 + T‐cell levels and prevented neurobehavioral deficits and neuronal loss among FIV + animals, compared to vehicle‐treated FIV + animals. Reduced neuronal neurosteroid synthesis was evident in lentivirus infections, but treatment with DHEA‐S limited neuroinflammation and prevented neurobehavioral deficits. Neurosteroid‐derived therapies could be effective in the treatment of virus‐ or inflammation‐mediated neurodegeneration.—Maingat, F. G., Polyak, M. J., Paul, A. M., Vivithanaporn, P., Noorbakhsh, F., Ahboucha S., Baker, G. B., Pearson, K., Power, C. Neurosteroid‐mediated regulation of brain innate immunity in HIV/AIDS: DHEA‐S suppresses neurovirulence. FASEB J. 27, 725–737 (2013). www.fasebj.org